Posttraumatic Stress Disorder (PTSD): Mechanisms and Possible Treatments - Asalgoo, S.; Jahromi, G.P.; Meftahi, G.H.; Sahraei, H. (Нейрофизиология, 2015)
Posttraumatic stress disorder (PTSD) is a debilitating mental condition occurring after a tragedy or a traumatic experience, such as rape, assault, natural disasters, war, car or plane accidents, etc. PSTD can cause a number of symptoms, such as fear, high anxiety, hyperarousal, bad dreams, night mares, etc., existing for a long time after the traumatic event. Within recent years, the spread of PTSD has been increased in the whole world, especially in Asia (Middle East), particularly among soldiers who have taken part in military conflicts. This situation confirms the importance of understanding the way of PTSD development and of the improvement of its treatment. This paper is a review of the literature related to the respective topics. Like other anxiety disorders, PTSD is related to disruption of the endocrine system, particularly disintegration of the hypothalamus-pituitary-adrenal axis (HPAA). People suffering from PTSD are characterized by elevated levels of corticotropinreleasing hormone, low basal cortisol levels, and enhanced negative feedback suppression of the HPAA. At present, certain plant-derived compounds are considered a new important source to treat PTSD. For example, remedies obtained from saffron are such possible means. According to our findings, saffron components may considerably affect some parts of the HPAA for reduction of stress-induced corticosterone release.